Impact of Influencer Trustworthiness and Financial Literacy on Herding Behavior with Risk Perception Mediating Variables of Indonesian Millennial Investors - Natahadi, Herdyawan; Makaryanawati, Makaryanawati; Keliwon, Kamarul Baraini (International Journal of Social Service and Research, 2024)
The ease of investment resulted in soaring number of millennial investors in Indonesia. Most investors in Indonesia are a beginner and do not know how to invest properly. Ignorance of investment encourages investors to find information and looking for role model then commonly leads to herding behaviour. This habit contradicts with traditional finance theory where investors supposed to invest rationally and avoid risk. This study will further explore the relationship between trustworthiness of financial influencers and financial literacy on herding behaviours with risk perception as mediating variables in millennial investors in Indonesia. Based on path analysis resulting the variable significantly influence each other directly or indirectly through mediating variable. Direct effect of trustworthiness financial influencer positively related with the herding behaviour, but the financial literacy negatively related with the herding behaviour. Indirectly Financial literacy level increased to increase risk perception and trustworthiness financial influencer vice versa. The decrease of risk perception leads millennial investor to herd and the increase of risk perception make investor more careful to make investment. There are still 33% of other factors influenced outside this study, for example gender, age, income, occupation and many other. Prior study has not examined the impact of a millennial follower’s trust on influencers to herding behaviours using risk perception as a mediating variable.